The Effects of Chemical Fertilizers on Composting process of Pistachio Waste - Marieh Nadi; Mohamad Moradi; Najmeh Pakdaman; Ebrahim Sedaghati; Amanollah Javanshah (International Journal of Recycling of Organic Waste in Agriculture)
Purpose A study was carried out on composting pistachio hull aided with chemical fertilizer. Recycling of pistachio wastes is one of the major agricultural way in pistachio producing country.Method The collected pistachio hull was allowed to decompose either naturally through composting or with the addition of chemical fertilizers. Biological and chemical properties with organic matter were monthly measured in both composting methods. The data was analyzed in a completely randomized design. Mean values were compared using Duncan's multiple range test in SPSS software (p < 0.05).Results Increasing chemical fertilizers reduced the microbial density and diversity during the composting, the concentration of the elements in both composting methods increased over time. The EC in both methods decreased over time from 6.95 to 6.17 dSm-1 in natural composting and 6.95 to 4.85 dSm-1 in adding of chemical fertilizers. The C: N ratios of the produced compost was found to be lowered in adding of chemical fertilizers during composting compared with those naturally composting treatment.Conclusion Addition of chemical compounds to the primary wastes could accelerate and improve the decomposition process and lead to faster composting as well as nutritional enrichment and lower C: N ratios, but it reduced microbial density and changed their diversities.